Managing abuse in sport: An introduction to the special issue. Issue 1 (February 2020) - Kavanagh, Emma; Adams, Adi; Lock, Daniel; Stewart, Carly; Cleland, Jamie
Highlights: This special issue presents a collection of papers that aim to enhance the field of managing abuse in sport. Five overarching themes across twelve papers are identified. Significant opportunities and challenges are presented in the management of abuse in sport. Opportunities and future directions for the management of abuse research proposed. Abstract: This special issue was designed to advance a research agenda focussed on the management of abuse in sport. Despite progress in the field, greater attention to the structures, policies, processes, practices, and sites in which abuse occurs is required. As such, there is a need for evidence-based solutions to improve the management of abuse and integrity in sport. The authors identified five overarching themes across the 12 papers included within the special issue: the harms and legacies of abuse; abuse in mediated environments; abuse of referees; frameworks that sustain abuse; and safeguarding. The articles included in this issue highlight the complexity of abuse in sporting spaces, the impact it can have on victims and the challenges faced in appropriately managing sporting spaces toward the reduction of harm. This special issue is driven by the authors' desire to promote integrity and enrich the sporting experience for all, with the hope of driving further research into the management of abuse and integrity in sport.